Identifying Indicators of Smartphone Addiction Through User-App Interaction. (October 2019) - Noë, Beryl; Turner, Liam D.; Linden, David E.J.; Allen, Stuart M.; Winkens, Bjorn; Whitaker, Roger M.
Abstract: We introduce a new approach to monitoring the activity of smartphone users based on their physical interactions with the interface. Typical events are taps, scrolling and typing, carried out to interact with apps. As compared to other measures, this directly encapsulates potential problematic physical smartphone behaviour as a signal. The approach contrasts against conventions such as self-reporting or timing activity sessions, and it focusses on active rather than passive smartphone activity. Using this alternative method, we collected all user interface interaction events from a sample of 64 participants over a period of 8 weeks, using a bespoke monitoring app called Tymer. User Smartphone Addiction was seen to significantly correlate with high levels of interaction with Lifestyle apps, particularly for female users. Interactions with Social apps in general were also associated with Smartphone Addiction. In particular, user interactions with Snapchat correlated with Smartphone Addiction, represented across all types of interface interaction. This is significant given the widespread usage of Snapchat by teenagers, and we hypothesise that the app's design provides a particularly strong pathway in support of Smartphone Addiction. Highlights: We assess the link between users' device interactions and Smartphone Addiction. The approach distinguishes between passive and active Smartphone usage. Lifestyle apps are associated with Smartphone Addiction, especially for female users. Social apps in general are associated with Smartphone Addiction. User interactions with Snapchat strongly correlate with Smartphone Addiction.